A FINE STRUCTURAL ANALYSIS OF CLEAVAGE INDUCTION AND FURROWING IN THE EGGS OF ARBACIA PUNCTULATA - Tilney, Lewis G. (The Rockefeller University Press, 1969)

(untitled)
A fine structural study has been carried out on the various formed elements present before, during, and after the first cleavage division, not only in normally developing Arbacia eggs, but also in eggs which have been induced to cleave prematurely by high-pressure centrifugation. The aim has been to ascertain whether or not any of the morphologically identifiable components may be involved in initiating the furrowing process. Also, attention has been given to the fine structure of the cytoplasmic cortex, particulary in the walls of the furrow, in the hope of reaching a better understanding of the mechanics of cleavage. The annulate lamellae and the membranous envelope of the nucleus are the only formed elements which disappear shortly before cleavage, not only in eggs undergoing normal division, but also in eggs which have been induced to cleave ahead of schedule by high-pressure, high-force centrifugation. Therefore, it is suggested as a tentative hypothesis that materials liberated upon disintegration of the nuclear membrane and the annulate lamellae play an essential role in initiating and effecting the furrowing reaction, especially since the stratification of these elements in experimentally induced eggs corresponds to the position of the developing furrow. Another of the membranous elements in the egg, the Golgi complex, shows considerable modification as a result of high-pressure centrifugation, but these structures do not undergo disintegration. Rather, they become curled into rounded bodies. The vacuole population is not greatly affected by inducing treatments. During cleavage, both naturally occurring and experimentally induced, a considerable number of 50 A filaments appear in the denser cytoplasmic cortex, but only in the walls of the furrow. These filaments are similar to those which have been demonstrated in a number of contractile cells. Accordingly, it is suggested that this fibrillar system may be actively involved in the development of the cleavage force.